344 LONG-TERM OUTCOMES FOR HIP FRACTURE PATIENTS WHO HAVE RECEIVED A PERIOD OF INPATIENT REHABILITATION. (25th October 2022) - Curtin, C; Cullen, S; Walsh, M; Keyes, S
Abstract: Background: Twenty-eight percent of the 3, 666 hip fractures reported by the Irish Hip Fracture Database (IHFD) in 2020 received a period of rehabilitation in an off-site facility nationally. Longer term outcomes for hip fracture patients are not yet included in the IHFD. This study aimed to describe recovery after hip fracture in patients admitted to a single inpatient rehabilitation facility. Methods: Patients who experienced hip fracture between January 2020 and July 2020 were followed up for one year after their fracture. Baseline data was collected in relation to age, pre-fracture residence and New Mobility Score (NMS) and clinical frailty score. Residence, NMS and quality of life (EQ-5D-5L) were collected by a clinical physiotherapist at 30 days, 120 days and 1 year after hip fracture. Data was inputted and analysed using Microsoft Excel. Results: Of 122 hip fracture patients admitted to rehabilitation, 103 were followed up. The average age of patients was 79, 66% were female. The mortality rate was 9% (n=9) at 1 year follow up. Pre-fracture, n= 98 lived at home. Of these patients, 67%, 82% and 83% had returned home by 30 days, 120 days and 1 year. Pre-fracture 53% had high mobility levels (NMS>6). Of these patient 4%, 27% and 34% had returned to this level by 30 days, 120 and 1 year. 70% of patients had a low mobility score (0-6 on NMS) and 30 % had a high mobility score (7-9) at 1 year follow-up. 56% and 4% of patients reported no pain and severe pain at 1 year post op, respectively. 45% of patients had no issues performing their usual activities and 4% had severe issues/an inability to perform their usual activities at 1 year. Conclusion: Our results show that recovery after hip fracture is slow with many not achieving baseline mobility or return to pre-fracture function within the first year.